Knowledge, attitude, and practice of school teachers regarding dental caries for school children in Navi Mumbai, India - Devendra Patil; Pooja Khakhar; Farhin Katge; Nikhil Bhanushali; Parin Bhanushali; Shantanu Deshpande (Wolters Kluwer Medknow Publications, 2022)
Background: Schools form a platform for molding habits in children, and teachers have a potential role in school-based dental education programs. Aim: The objective of this study was to evaluate level of knowledge, attitude, and practice of school teachers regarding dental caries in children in schools of Navi Mumbai. Materials and Methods: A cross-sectional survey was conducted among school teachers in Navi Mumbai. A total of 554 teachers completed the questionnaire, which included questions on demographic data, knowledge about etiology of dental caries, its prevention, their attitude, practice, and role of teachers in the management of dental caries. The data were analyzed using Chi-square test. Results: A total of 554 school teachers filled the questionnaire. The number of female teachers (84.8%) was very high as compared to male teachers. Approximately 60% of study population considered bacteria and amount of sweets consumed as the cause of dental caries. More than 52% considered eating less sugar as one of the ways to prevent caries. Furthermore, 57.4% of teachers were willing to implement future training programs on caries prevention. Conclusion: Knowledge regarding dental caries among school teachers in Navi Mumbai was adequate. Teachers were willing to participate in oral health promotion training programs.